Effects of active static stretching in a patient with COPD after complication by COVID-19, case report - Nascimento Folha, Pablo; Pereira Frank Bacurau, Reury (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: COPD, called Chronic Obstructive Non-transmitted Pulmonary Disease, is a disease that causes severe sequelae in the respiratory system, which in combination with other types of viruses such as covid-19 aggravates the disease, with major effects on the locomotor system due to saturation instabilities. The main victims of the disease are elderly smokers and ex-smokers of both sexes. In more severe cases, there is a need for continuous treatment with oxygen therapy, limiting the quality of life and physical activity of the elderly. Objective: Physical activity is an alternative non-pharmacological treatment to help the recovery of the individual with severe COPD, minimizing the complications of the disease. Method: The study aims to describe the case of a 77-year-old elderly man, ex-smoker for 17 years, with severe sequelae post COPD-19 in the respiratory system, dependent on oxygen therapy for great instability of mean saturation below 70%, with reflexes on the locomotor system, having difficulties in locomotion. In this case, to keep him active, active static stretching exercises were proposed for five consecutive days. Results: After five consecutive days of active stretching, the results were positive, increasing saturation by an average of 1.75%, reaching 89.79% without the help of oxygen therapy, which was enough to reduce dyspnea, wean him off oxygen therapy, and improve his mobility and quality of life. Conclusion: that active static stretching is beneficial for severe cases of COPD, minimizing complications and reducing the use of oxygen therapy.